The Meaning of the Term “Gus” in the Case of Gus Miftah: A Peircean Semiotic Analysis - Pitoyo Pitoyo; Rizky Wulan Ramadhani (Jurnal Komunikasi dan Bisnis, 2025)
Miftah Maulana Habiburrahman, widely known as Gus Miftah, is a preacher and the leader of the Ora Aji Islamic Boarding School in Sleman, Yogyakarta. A viral video in which he mocked an iced tea seller using the word “goblok” sparked public backlash and raised questions regarding his use of the honorific title “Gus.” This study aims to analyze the meaning of the word Gus attached to Miftah using Charles Sanders Peirce’s semiotic framework. Employing a qualitative method through literature review and historical texts, the study explores the genealogical claims linking Miftah to Kiai Ageng Muhammad Hasan Besari. Using Peirce’s triadic model—Representamen, Object, and Interpretant—the findings indicate that Miftah functions as the object, Gus as the representamen, and the interpretant refers to a lineage of prominent kiai figures affiliated with Nahdlatul Ulama (NU), used as personal branding. However, based on available records and family statements, Miftah has no blood relation to Kiai Ageng Besari and does not descend from any NU kiai lineage, casting public doubt on his claim to the Gus title. The study urges the public to critically assess religious figures' claims to noble lineage and suggests further research into the genealogy of Kiai Ageng Besari, given gaps in available records since the 1960s.